Development of Copper-Aluminum Layered Double Hydroxide in Thin Film Nanocomposite Nanofiltration Membrane for Water Purification Process - Muhammad Hanis Tajuddin; Muhammad Hanis Tajuddin; Norhaniza Yusof; Norhaniza Yusof; Ihsan Wan Azelee; Ihsan Wan Azelee; Wan Norharyati Wan Salleh; Wan Norharyati Wan Salleh; Ahmad Fauzi Ismail; Ahmad Fauzi Ismail; Juhana Jaafar; Juhana Jaafar; et al. (Frontiers in Chemistry, 2019)
This study aims to fabricate a thin film composite (TFC) membrane, modified with copper-aluminium layered double hydroxide (LDH) nanofillers via interfacial polymerization technique for nanofiltration (NF) processes. It was found that Cu-Al LDH nanofillers possessed layered structured materials with typical hexagonal plate-like shape and positive surface charge. The study revealed that TFN membrane exhibits a relatively smooth surface and a less nodular structure compared to pristine TFC membrane. The contact angle of TFN progressively decreased from 54.1° to 37.25°, indicating enhancement in surface hydrophilicity. Moreover, the incorporation of LDH nanofillers resulted in a less negative membrane as compared to the pristine TFC membrane. The best NF performance was achieved by TFN2 membrane with 0.1° of Cu-Al LDH loading and a water flux of 7.01 Lm-2h-1.bar. The addition of Cu-Al LDH resulted in excellent single salt rejections of Na2SO4 (96.8%), MgCl2 (95.6%), MgSO4 (95.4%), and NaCl (60.8%). The improvement in anti-fouling properties of resultant TFN membranes can be observed from the increments of pure water flux recovery and normalized water flux by 14% and 25% respectively. The findings indicated that Cu-Al LDH is a promising material in tailoring membrane surface properties and fouling resistance. The modification of the LDH-filled TFN membrane shows another alternative to fabricating a high-performance composite membrane, especially for water softening and partial desalination process.